Bringing Cultural Diversity to Feminist Psychology: Theory, Research, and Practice. 1995
DOI: 10.1037/10501-010
|View full text |Cite
|
Sign up to set email alerts
|

American Indian women and psychology.

Abstract: The ways of Native American women who choose to follow the healing path include the following: the way of the daughter, the way of the householder, the way of the mother, the way of the teacher, and the way of the wise woman. Each of these ways toward spiritual development, or "disciplines that accord with the age of the aspirant and her duties within the sacred wheel of life" (Allen, 1991, p. lo), leads one to ever more specialized modes of work. We have accepted this developmental framework as a guide for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Further, even studies of groups who are primarily American Indian (e.g., Maguire, 1987) may attend little to issues of race or culture. There is a great need for more investigations of domestic violence among American Indians that takes into account the culture and context of Indian life (LaFramboise, Choney, James, & Running Wolf, 1995b).…”
Section: Domestic Violence In Native North Americamentioning
confidence: 99%
See 3 more Smart Citations
“…Further, even studies of groups who are primarily American Indian (e.g., Maguire, 1987) may attend little to issues of race or culture. There is a great need for more investigations of domestic violence among American Indians that takes into account the culture and context of Indian life (LaFramboise, Choney, James, & Running Wolf, 1995b).…”
Section: Domestic Violence In Native North Americamentioning
confidence: 99%
“…It is likely that, as in other areas, there was considerable variability among tribes, and that unrecognized cultural differences account for some of the disagreement. The one area of agreement is that rates of domestic violence appear to have risen dramatically in the last 150 years (Chester et al, 1994;DeBruyn et al, 1990;Gunn Allen, 1990;LaFramboise et al, 1995b). Contact with Westerners has had many negative consequences, including increased domestic violence rates, probably due in part to profound losses in the traditional statuses and roles of both men and women (Wolk, 1982).…”
Section: Domestic Violence In Native North Americamentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescent American Indian girls are an especially vulnerable population to unwanted teen pregnancy, sexual abuse, alcohol and drug abuse, depression, and eating disorders (LaFromboise, Choney, James, & Running Wolf, 1995). Indeed, a 1989 Indian Adolescent Health Survey report found that young American Indian girls in boarding schools are more prone to depression and that 20% of all American Indian girls have attempted suicide (LaFromboise et al, 1995).…”
Section: Gender and Racial Identities: The Challenge Of Oppression An...mentioning
confidence: 99%